2018
DOI: 10.1002/cctc.201800172
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hierarchical V2O5 Nanorods on TiO2 Nanofibers and Their Enhanced Photocatalytic Activity under Visible Light

Abstract: We report photocatalytic activities of a set of mesoporous, hierarchical “nanorods‐on‐nanofiber” heterostructures produced from the organization of vanadium pentoxide (V2O5) nanorods on titanium dioxide (TiO2) nanofibers fabricated using gas jet fiber (GJF) spinning process. The precursor nanofibers spun from solutions of poly(vinylpyrrolidone), titanium tetraisopropoxide, and vanadium oxytriisopropoxide are calcined at 500–600 °C in air to yield the above hierarchical nanostructures. The calcination temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 71 publications
0
43
0
Order By: Relevance
“…have been extensively studied as catalysts for the removal of VOCs because they are inexpensive and plentiful. [16][17][18][19][20][21][22][23] Tricobalt tetraoxide (Co 3 O 4 ), one of the most promising materials, has been used in catalytic oxidation, lithium-ion batteries as energy storage materials, sensor devices and other important fields. [24][25][26][27][28] A number of studies have focused on Co 3 O 4 for the catalytic oxidation of VOCs due to its high catalytic activity, low cost and environmental benignity.…”
Section: Introductionmentioning
confidence: 99%
“…have been extensively studied as catalysts for the removal of VOCs because they are inexpensive and plentiful. [16][17][18][19][20][21][22][23] Tricobalt tetraoxide (Co 3 O 4 ), one of the most promising materials, has been used in catalytic oxidation, lithium-ion batteries as energy storage materials, sensor devices and other important fields. [24][25][26][27][28] A number of studies have focused on Co 3 O 4 for the catalytic oxidation of VOCs due to its high catalytic activity, low cost and environmental benignity.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the oxidation of ethanol that leads to breaking down the C-C bonds in ethanol; then the holes in the valance band attack the hydrogen atom. We conclude that CH 3 COO − and HCOO − intermediates are accumulated during photo-oxidation, which led to the formation of CO 2 and H 2 O as the results of ethanol oxidation 13 . During the photocatalytic oxidation reaction, the effective hot holes are formed after the irradiation of UV-vis light that might be combined with H 2 O to yield hydroxyl radicals (.OH).…”
mentioning
confidence: 81%
“…The previous reports revealed that the photocatalytic reduction of CO 2 was enhanced using selective behavior of a catalyst that helped to reduce the CO 2 to methanol 38 . Besides, notably, the information about the reaction with oxygen in semiconductor materials emerged 13,39,40 . Interestingly, the V 2 O 5 -TiO 2 semiconductor was used to study the ethanol-oxidation by DRIFT, showing the enhanced photocatalytic activity under visible light 13 .…”
mentioning
confidence: 99%
“…The well-defined diffraction rings in the selected electron area diffraction (SEAD) can be indexed as (100), (101), (102), (110) planes of MnO 2 ( Figure S3), which is consistent with the XRD results. The XRD results show the formation of manganese dioxide and a small amount of MnO 2 doping in the HTM spheres [37]. XPS analysis is used to obtain the chemical state and bonding environment of HTM, helping us understand basic information about the interaction between TiO 2 and MnO 2 .…”
Section: The Preparation and Structure Of Tio 2 /Mno 2 (Htm) Spheresmentioning
confidence: 99%
“…For commercial active MnO 2 (CAM), the degradation rate of phenol is as low as 18% under PMS. By contrast, the removal rate of phenol is as high as 92% under the same oxidation conditions for the as-synthesized HTM hollow spheres because its large surface-to-volume ratio (HTM: 53.7827 m 2 /g; MnO 2 ( Figure S4): 25.7805 m 2 /g) and hollow/porous characteristics facilitate the access of reactant phenol molecules [30,37]. Unfortunately, even if the PMS is added again after 60 min ( Figure S5), the removal of phenol does not increase accordingly.…”
Section: Chemical Oxidation Activity Of Htmmentioning
confidence: 99%